Technology of Intelligent Control of Unmanned Aerial Vehicles Monitoring in the Airspace Using 5G Cellular Networks - Odarchenko, R.S.; Volkov, O.Ye.; Simakhin, V.M.; Gospodarchuk, O.Yu. (Cybernetics and computer engineering, 2020)
The purpose of the paper is to analyze the state of the UAV market and related legislation in the world and Ukraine; to develop the technology for intelligent control of UAV monitoring using cellular networks; to prepare guidelines for the implementation and application of the system. Results. The technology of intelligent monitoring of UAVs with the use of a modern 5G cellular network was developed. The use of the fifth generation network provides high data transfer speeds with ultra-low latency and meets all the necessary security requirements. The technology of intelligent control of UAV monitoring consists of separate methods, which are executed in the monitoring center, data processing center and in the supervisory control and data acquisition system. The use of cellular base stations for primary data processing and filtering speeds up the events processing in the UAV network. Мета статті — проаналізувати стан ринку БпЛА та пов’язаного законодавства у світі та Україні, розробити технологію інтелектуального керування моніторингом БпЛА з використанням стільникових мереж, підготувати вказівки щодо імплементації та застосування системи. Результати. З метою розв’язання проблеми моніторингу та реєстрації БпЛА проаналізовано можливість використання стільникових мереж нового покоління для забезпечення реєстрації та безперервного моніторингу БпЛА. Як результат, для розвитку системи зв'язку було вибрано сучасну стільникову мережу 5G, яка є найбільш прогресивною серед усіх сучасних альтернатив.